Rational Choice of Antibiotics and Media for Mycobacterium avium Complex Drug Susceptibility Testing - Jaffré, Jérémy; Aubry, Alexandra; Maitre , Thomas; Morel, Florence; Brossier, Florence; Robert, Jérôme; Sougakoff, Wladimir; Veziris, Nicolas; , the CNR-MyRMA (Centre National de Référence des Mycobactéries et de la Résistance des Mycobactéries aux Antituberculeux) (Frontiers in Microbiology, 2020)
The Clinical and Laboratory Standards Institute recommends the use of Mueller Hinton (MH) medium to perform drug susceptibility testing (DST) of Mycobacterium avium complex (MAC) using the microdilution method. For MAC, there has been no study on the impact of media on the determination of minimum inhibitory concentrations (MICs) of antibiotics other than clarithromycin. This study aimed at determining the impact of two media used for DST of MAC and at augmenting the number of pertinent MICs for MAC species encountered in clinical practice. MICs of antibiotics used for the treatment of MAC infections were determined for 158 clinical MAC isolates (80 M. avium, 40 M. intracellulare, 35 M. chimaera, two M. yongonense and one M. timonense) in MH and 7H9 broths using the SLOMYCO SensititreTM system (TREK Diagnostic Systems, East Grinstead, UK). The modal MICs determined in both media were the same for linezolid, moxifloxacin, rifabutin and amikacin but not for clarithromycin, rifampin and ethambutol. The kappa test for MICs converted to susceptibility categories showed an excellent agreement for clarithromycin, a moderate agreement for linezolid and a weak agreement for moxifloxacin and amikacin. For amikacin, 7H9 allowed a better distinction (fewer intermediate strains) of wild-type populations than MH. Existing breakpoints for linezolid and moxifloxacin reduced the apparent distribution of MICs for wild-type populations. The only breakpoints that can be used rationally are those for amikacin and clarithromycin. For amikacin, 7H9 performs better than MH, whereas both media perform equally for clarithromycin. Given that testing in 7H9, as opposed to MH, allows easier MIC measurements and yields greater reproducibility, we propose the use of 7H9 medium for DST of MAC.